Silk fibroin artificial blood vessel with biomimetic gradient structure and preparation and application thereof

CN122665191BActive Publication Date: 2026-10-27CHONGQING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611149473.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27
Estimated Expiration
2046-07-31

AI Technical Summary

Technical Problem

[0005]为克服现有技术中人工血管结构均一、无法同时满足内皮层抗凝与中膜层重塑需求等问题,本发明通过创新的电泳工艺,制备出了一种内层致密、外层疏松、梯度结构连续、界面结合牢固的一体化丝素蛋白人工血管

Benefits of technology

[0069]1、现有技术中的人工血管(如静电纺丝多层复合或编织复合)通常存在层间结合力弱的问题。多层结构主要依靠物理缠结或范德华力结合,在体内动态应力(如脉动血流、血管弯曲)下容易发生层间剥离,导致血管破裂或血栓形成。本发明以丝素蛋白作为构建人工血管的单一生物材料,通过电泳沉积工艺,在电场驱动下自组装形成内层致密而外层疏松的一体化结构,内层和外层呈现连续的梯度过渡,之间没有明显的物理界面。这种结构消除了层间剥离的风险,确保了血管壁在长期植入后的力学完整性和结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122665191B_ABST
    Figure CN122665191B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of biological medicine, and particularly relates to a silk fibroin artificial blood vessel with a biomimetic gradient structure and a preparation and application thereof. The preparation method of the silk fibroin artificial blood vessel specifically comprises the following steps: preparing a silk fibroin solution and performing calcium ion induction treatment to obtain a silk fibroin gel homogenate; and the obtained silk fibroin gel homogenate is subjected to intermittent electrophoresis deposition and crosslinking fixation to obtain the silk fibroin artificial blood vessel with the biomimetic gradient structure. The artificial blood vessel prepared by the application has a gradient structure with a continuously changed pore size and porosity from inside to outside, the inner layer is compact and smooth, which is beneficial to rapid endothelialization; the outer layer is loose and porous, which is beneficial to smooth muscle cell infiltration, nutrient exchange and tissue media remodeling. The blood vessel structure is integrally formed, the interlayer combination is firm, the blood vessel structure can simulate the cell microenvironment and the biological microenvironment of a natural blood vessel, and supports ordered repair and function reconstruction of the blood vessel after implantation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical technology, specifically relating to a silk fibroin artificial blood vessel with a biomimetic gradient structure and its preparation and application. Background Technology

[0002] Vascular replacement materials have significant clinical value in the treatment of cardiovascular diseases and in tissue engineering. Natural blood vessels possess a highly complex hierarchical structure: the endothelium maintains blood compatibility and prevents thrombosis, the media provides essential mechanical support and participates in tissue remodeling, and the outer layer facilitates substance exchange through interaction with surrounding tissues. However, existing artificial or tissue-engineered blood vessels are mostly homogeneous porous structures, resulting in a lack of a complete three-layered structure for vascular repair. Therefore, constructing multilayered artificial blood vessels with biomimetic gradient structures is an important direction in tissue engineering research.

[0003] Currently, the construction of layered artificial blood vessels often employs methods such as electrospinning multilayer composites, a combination of weaving and spinning, or surface coating. However, these traditional methods have inherent limitations in achieving biomimetic gradient structures. First, in the electrospinning multilayer composite process, different functional layers are prepared stepwise and stacked layer by layer, with each subsequent layer of fiber stacked on top of the previous one. The binding force mainly relies on the physical entanglement and van der Waals forces between nanofibers. This mechanical bonding is prone to loosening under long-term complex dynamic stress environments in vivo, such as pulsating blood flow, vascular tortuosity, and the mechanical constraints of surrounding tissues, leading to interlayer delamination, disrupting the integrity of the blood vessel wall, and potentially causing vascular rupture. For example, the poly(glycerol sebacic acid ester) / polyvinyl alcohol (PGS / PVA) electrospun scaffold disclosed by Caroline F et al. in "Suturable elastomeric tubular grafts with patterned porosity for rapid vascularization of 3D constructs" illustrates this. Secondly, in methods combining weaving and spinning, the woven layer is typically a synthetic polymer, such as polyester, which is a heterogeneous material from the spun layer (which may be collagen, silk fibroin, etc.). Their coefficients of thermal expansion, degradation rates, and properties such as elastic modulus and elongation at break differ. During preparation and use, this difference leads to an imbalance of forces at the interface, causing interlayer damage. Furthermore, as the materials undergo hydrolysis and enzymatic degradation within the body, the different degradation rates of the different materials exacerbate stress concentration at the interface, accelerating interface damage. For example, Huang Songtao et al. reported two types of blended composite fiber membranes in their paper, "Preparation and Mechanical Properties of Electrospun Fibers of ...

[0004] Furthermore, the different fabrication processes and material systems of different layers result in spatial discontinuities in the structure, making it difficult to achieve a continuous gradient distribution from the intima to the adventitia. The growth and function of vascular cells are highly dependent on their microenvironment. Smooth muscle cells and fibroblasts require orderly migration, arrangement, and matrix secretion along the gradient structure of the extracellular matrix. Discontinuous structural interfaces disrupt the directional migration and arrangement of cells, potentially leading to abnormal cell aggregation at the interface, forming pathological structures, and hindering the transport of nutrients and metabolic waste. Particularly in the repair of small-diameter vessels (less than 6 mm in diameter), the high shear stress of blood flow and the susceptibility to intimal hyperplasia place even more stringent demands on the endothelialization rate and antithrombotic properties of artificial blood vessels. Existing uniform porous structures or discontinuous layered structures often fail to meet these requirements. Therefore, developing a method for fabricating artificial blood vessels that can be integrally molded, with strong interlayer bonding and a continuous gradient structure is particularly urgent. Summary of the Invention

[0005] To overcome the problems of homogeneous artificial blood vessel structures and the inability to simultaneously meet the requirements of endothelial anticoagulation and medial remodeling in existing technologies, this invention utilizes an innovative electrophoresis process to fabricate an integrated silk fibroin artificial blood vessel with a dense inner layer, a loose outer layer, a continuous gradient structure, and strong interfacial bonding. This blood vessel not only solves the problems of interlayer delamination and structural discontinuity in existing technologies, but also achieves the dual functions of rapid endothelialization and promotion of smooth muscle cell infiltration by simulating the microenvironment of natural blood vessels, providing an ideal solution for the repair and reconstruction of small-diameter vascular defects.

[0006] One of the objectives of this invention is to provide a method for preparing silk fibroin artificial blood vessels with a biomimetic gradient structure.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] A method for preparing silk fibroin artificial blood vessels with a biomimetic gradient structure includes the following steps:

[0009] S1: Prepare a silk fibroin solution and perform calcium ion induction treatment to obtain a silk fibroin gel homogenate;

[0010] The calcium ion-induced treatment includes: concentrating the silk fibroin solution, adjusting the pH to 7.2±0.2, and adding CaCl2 stock solution to induce the β-sheet transition of silk fibroin; the final concentration of the CaCl2 stock solution is 50 mM.

[0011] S2: The silk fibroin gel homogenate obtained in S1 was deposited by intermittent electrophoresis and cross-linked and fixed with glutaraldehyde to obtain a silk fibroin artificial blood vessel with a biomimetic gradient structure.

[0012] The intermittent electrophoretic deposition includes:

[0013] 1) The silk fibroin gel homogenate is injected into a cylindrical electrophoresis tank for electrophoretic deposition. After power is turned off and the tank is allowed to stand, silk fibroin gel homogenate is added. The cylindrical electrophoresis tank is formed by using a cylindrical acrylic tube as a mold, with shallow grooves opened on its inner wall and a platinum sheet embedded as a cathode. A zinc rod is fixed at the center of the mold as an anode to form a cylindrical electrophoresis tank.

[0014] 2) Repeat the electrophoresis, settling and displacement feeding operations in step 1) for a total of 4 rounds; through the electrophoretic deposition process, under the drive of the electric field, a self-assembled integrated structure with a dense inner layer and a loose outer layer is formed, and the inner and outer layers show a continuous gradient transition.

[0015] In steps 1)-2), the initial voltage for electrophoretic deposition is 15V, and the initial electrophoresis time is 60s; during the cyclic deposition process, the voltage gradually decreases to 11V, and the electrophoresis time decreases by 6 seconds per cycle.

[0016] Furthermore, in S1, the method for preparing the silk fibroin solution includes: obtaining a purified silk fibroin solution by degumming, dissolving, and dialysis of silkworm cocoons.

[0017] Preferably, the dissolving solvent is a mixed solution of calcium chloride, ethanol and deionized water, wherein the molar ratio of calcium chloride, ethanol and deionized water is 1:2:8.

[0018] Preferably, the silkworm pupae are first removed from the cocoons, then cut into small pieces of 2-5mm, and then degummed.

[0019] Preferably, the degumming process involves placing the silkworm cocoon block in a sodium carbonate solution and boiling it at 95-100°C for 20-60 minutes to remove sericin.

[0020] More preferably, the degumming heating time is 30 minutes.

[0021] More preferably, the concentration of the sodium carbonate solution is 0.01~0.1M, more preferably 0.02M.

[0022] Preferably, after degumming, the cocoon blocks are repeatedly rinsed with clean water, and then dehydrated and dried.

[0023] Preferably, the dissolution temperature is 75-85℃.

[0024] More preferably, the dried silk fibroin raw material is added to a dissolving solvent and heated and stirred until the raw material is completely dissolved to obtain a clear and homogeneous silk fibroin solution.

[0025] Preferably, the dialysis temperature is 2~8℃ and the dialysis time is 2~5 days; more preferably, dialysis is performed at 4℃ for 3 days.

[0026] Preferably, deionized water is used as the dialysis fluid in the dialysis process.

[0027] Preferably, the dialysis fluid is changed every 10 to 15 hours during dialysis, and more preferably every 12 hours.

[0028] Preferably, the molecular weight cutoff of the dialysis bag is 3.5 kDa.

[0029] Preferably, the dialysis bags are boiled in boiling water for 5 minutes before use, and then thoroughly cleaned with deionized water.

[0030] Preferably, in the calcium ion induction treatment described in S1, the mass concentration of the concentrated silk fibroin solution is 2-5 wt%.

[0031] More preferably, the concentration of the silk fibroin solution is 3 wt%.

[0032] Preferably, in the calcium ion-induced treatment described in S1, the concentration specifically includes: loading the dialysis-purified silk fibroin solution into a concentration tube with a molecular weight cutoff of 3.5 kDa, and centrifuging and concentrating it at 2~8℃ and 4000~8000 r / min until the solution reaches a suitable mass concentration.

[0033] Preferably, in S1, a dilute hydrochloric acid (HCl) or sodium hydroxide (NaOH) solution is used to adjust the pH under magnetic stirring.

[0034] Preferably, in S1, the reaction conditions include: constant temperature incubation at 37°C and 150 rpm for 24 hours.

[0035] More preferably, in S1, the concentration of the CaCl2 stock solution is 1M.

[0036] Further, the silk fibroin solution after calcium ion induction treatment is diluted to a concentration of 1-5% (w / v) and kept in a constant temperature water bath at 50-70℃ for 2-5 hours to obtain silk fibroin hydrogel; the silk fibroin hydrogel is broken up to prepare a flowable homogenous precursor solution, namely the silk fibroin gel homogenate.

[0037] More preferably, in S1, the silk fibroin solution after calcium ion induction treatment is diluted to a concentration of 2% and kept in a constant temperature water bath at 60°C for 3 hours to obtain a silk fibroin hydrogel; the silk fibroin hydrogel is broken to obtain a silk fibroin gel homogenate.

[0038] Preferably, in S2, the method for constructing the cylindrical electrophoresis tank includes: using a cylindrical acrylic tube as a molding mold, opening shallow grooves on its inner wall, and embedding platinum sheets as cathodes; fixing a zinc rod at the center of the mold as an anode to form a cylindrical electrophoresis tank.

[0039] More preferably, perforations are made at the center of the upper silicone foam plug and at the bottom of the mold to ensure that the zinc rod is in the center of the mold, thereby forming a uniform radial electric field around the central anode in the internal cavity of the mold.

[0040] More preferably, the inner diameter of the cylindrical acrylic tube is 12 to 16 mm, and more preferably 14 mm.

[0041] More preferably, the diameter of the zinc rod is 1-2 mm, and even more preferably 1 mm.

[0042] Preferably, in S2, each round is left to stand still for 30 seconds.

[0043] Preferably, after each settling period, the residual homogenate that did not participate in the deposition is removed from the electrophoresis tank, and then an equal amount of freshly prepared silk fibroin gel homogenate is added.

[0044] Preferably, in S2, after the last cycle is completed, a stabilization molding step is also included: electrophoresis is performed again at 12V for 90s.

[0045] More preferably, after the initial completion of the pipe structure, an appropriate amount of silk fibroin gel homogenate is added, and electrophoresis is performed again at 12V for 90s to stabilize the formed structure.

[0046] As a preferred method, the specific steps of electrophoretic deposition are as follows:

[0047] ① Initial electrophoresis: voltage 15V, electrophoresis time 60 seconds, resting time 30 seconds;

[0048] ② Loop:

[0049] First cycle: voltage 14V, electrophoresis time 54 seconds, resting time 30 seconds;

[0050] Second cycle: voltage 13V, electrophoresis time 48 seconds, resting time 30 seconds;

[0051] Third cycle: voltage 12V, electrophoresis time 42 seconds, resting time 30 seconds;

[0052] Fourth cycle: voltage 11V, electrophoresis time 36 seconds, resting time 30 seconds;

[0053] ③Stable molding: voltage is 12V, electrophoresis time is 90 seconds.

[0054] More preferably, after the fourth round of static feeding, electrophoresis is performed at 10V for 30 seconds. After electrophoresis, the material is allowed to stand for 30 seconds to remove the residual homogenate in the electrophoresis tank. At this point, the pipe structure has been initially formed. Then, the overall shape is further solidified on this basis.

[0055] Preferably, in S2, glutaraldehyde solution is used for cross-linking fixation; the concentration of the glutaraldehyde solution is 2%; the cross-linking time is 12 hours; and the cross-linking temperature is 4°C.

[0056] More preferably, the prepared layered silk fibroin tube is completely immersed in glutaraldehyde crosslinking solution to ensure that no air bubbles adhere to the tube, and then crosslinking treatment is carried out under light-protected conditions; after crosslinking is completed, the tube is taken out and rinsed repeatedly with deionized water 3-5 times, each time for 10 minutes, to completely remove residual glutaraldehyde, and obtain silk fibroin artificial blood vessel with biomimetic gradient structure.

[0057] The second objective of this invention is to provide a silk fibroin artificial blood vessel with a biomimetic gradient structure prepared by the aforementioned method.

[0058] Preferably, the artificial blood vessel is a small-diameter artificial blood vessel.

[0059] Preferably, the inner diameter of the artificial blood vessel is 1-4 mm.

[0060] More preferably, the inner diameter of the artificial blood vessel is 2 to 2.5 mm.

[0061] Preferably, the outer diameter of the artificial blood vessel is 6-10 mm.

[0062] In some embodiments, the artificial blood vessel has an inner diameter of 2.12 mm and an outer diameter of 9.67 mm.

[0063] Preferably, the artificial blood vessel has an integrated layered structure.

[0064] The silk fibroin artificial blood vessel has a tight inner and outer layer with no obvious interface defects, achieving a unified function of structural support, cell adaptation, and material delivery. The layered structure constructed by the electrophoretic properties of the silk fibroin β-sheet can better simulate the physiological structure and functional characteristics of natural blood vessels, providing a good foundation for subsequent research on the biocompatibility of artificial blood vessel materials.

[0065] More specifically, the inner dense structure directly corresponds to the luminal surface of the artificial blood vessel in contact with blood. This smooth, dense surface provides a good base for the adhesion, spread, and directional growth of vascular endothelial cells, facilitating the rapid formation of a complete endothelial barrier and enhancing the antithrombotic ability of the artificial blood vessel. Simultaneously, the high proportion of β-sheet protein in the dense structure provides excellent mechanical support, resisting the shear forces of blood flow and ensuring the long-term stability of the artificial blood vessel. The outer loose structure directly contacts the host tissue. This layer has abundant interconnected pores, providing ample space for the adhesion, migration, and proliferation of vascular smooth muscle cells. Cells can easily infiltrate the pores, improving the problem of cell inward growth that is difficult in dense structures. Furthermore, the porous structure significantly improves the mass transfer efficiency of bioactive substances such as growth factors, nutrients, and cytokines, providing a suitable environment for smooth muscle cell growth and proliferation, promoting the remodeling of the artificial blood vessel in vivo, and forming a complete and reliable vascular media.

[0066] Preferably, the inner layer of the artificial blood vessel has a dense structure with low porosity and a pore size of approximately 0.1-1 μm, which is suitable for endothelial cell adhesion and spreading. The intermediate transition region of the artificial blood vessel exhibits a continuous transition from dense to loose, with a pore size of 1-10 μm and a gradient increasing trend. This transition region simulates the mechanical gradient characteristics between the intima and media of natural blood vessels, which is beneficial for stress buffering and transmission. The outer layer of the artificial blood vessel presents a three-dimensional interconnected porous network structure with high porosity and a pore size of approximately 10-50 μm, which is suitable for the migration and infiltration of smooth muscle cells and fibroblasts.

[0067] A third objective of this invention is to provide the application of the aforementioned silk fibroin artificial blood vessel in the preparation of tissue engineering materials and / or in medical devices for the treatment of cardiovascular and cerebrovascular diseases.

[0068] The beneficial effects of this invention are as follows:

[0069] 1. Existing artificial blood vessels (such as electrospun multilayer composites or braided composites) often suffer from weak interlayer bonding. Multilayer structures rely primarily on physical entanglement or van der Waals forces for bonding, making them prone to interlayer delamination under dynamic stress in vivo (such as pulsating blood flow or vascular tortuosity), leading to vascular rupture or thrombosis. This invention uses silk fibroin as the single biomaterial for constructing artificial blood vessels. Through electrophoretic deposition, driven by an electric field, it self-assembles into an integrated structure with a dense inner layer and a loose outer layer. The inner and outer layers exhibit a continuous gradient transition without a clear physical interface. This structure eliminates the risk of interlayer delamination, ensuring the mechanical integrity and structural stability of the blood vessel wall after long-term implantation.

[0070] 2. This invention, through process control, constructs a biomimetic gradient structure artificial blood vessel. Its inner layer is rich in β-sheet structures, providing mechanical strength and a smooth inner surface; the outer layer has interconnected pores, facilitating cell ingrowth and substance exchange. Specifically, the inner layer of this artificial blood vessel has a dense structure with a smooth surface and lower porosity than the outer layer. It is rich in silk fibroin with a β-sheet conformation, providing an ideal biological interface for the adhesion and spreading of vascular endothelial cells, promoting the rapid formation of a complete endothelial monolayer, thereby improving blood compatibility. Simultaneously, this dense structure provides the primary mechanical support, endowing the tube with excellent tensile and burst resistance, able to withstand the shear forces of blood flow, and ensuring morphological stability during long-term implantation. The outer layer of the artificial blood vessel has a loose and porous structure with interconnected macroscopic and microscopic pores, and its porosity is significantly higher than that of the inner layer. This structure provides physical space for the migration, infiltration, and three-dimensional proliferation of vascular smooth muscle cells, effectively solving the technical problem of cells being unable to grow inward in dense materials. Its open pore network greatly promotes the biomass transfer efficiency of oxygen, nutrients, and various growth factors (such as VEGF, PDGF, etc.), creating a favorable microenvironment for cell metabolism and extracellular matrix secretion, thereby promoting in-situ regeneration and functional remodeling of the vascular endothelial tissue.

[0071] 3. The preparation method of this invention achieves structural uniformity and repeatability by precisely controlling electrophoresis parameters, such as voltage, time, intermittent electrophoresis, and feeding strategy. This invention employs a low voltage of 8-20V and an intermittent energizing strategy to control the thickness and density of the deposition layer, resulting in a dense inner layer and a porous outer layer in the prepared artificial blood vessel material, effectively mimicking the gradient structure of natural blood vessels.

[0072] 4. This invention uses silk fibroin as the single biomaterial for constructing artificial blood vessels, through Ca... 2+ Induction, intermittent electrophoresis, and glutaraldehyde crosslinking further enhance the material's water resistance, stability, and biocompatibility. Experimental data show that the layered artificial blood vessels prepared in this invention have a hemolysis rate of less than 5% and no significant hemolytic toxicity, indicating that they have good blood compatibility and are suitable for implantation.

[0073] 5. This invention provides an artificial blood vessel based on silk fibroin that can induce the directional growth of endothelial cells and smooth muscle cells in a specific region. This artificial blood vessel constructs a layered tubular structure with uniform structure and interfacial bonding layer by layer, regulating the pore size and porosity gradient of its wall from the inside out. This achieves a dense inner layer for rapid endothelialization and a loose outer layer to promote smooth muscle cell infiltration and in vivo vascular remodeling, thereby constructing a functionally complete intima-media biomimetic structure. This artificial blood vessel is suitable for the repair and reconstruction of small-diameter vascular defects and can effectively reduce the risk of thrombosis. Attached Figure Description

[0074] Figure 1This invention presents the fabrication process and flowchart for layered artificial blood vessels. Under neutral conditions, silk fibroin molecules carry a negative charge. The present invention employs an intermittent electrophoretic deposition strategy: first, a voltage of 15 V is applied for 60 s; then, using 10 V as the reference voltage, the process is repeated 4 times with a single cycle duration decreasing by 6 s; finally, a voltage of 12 V is applied for enhanced treatment for 90 s. Under the action of a radial electric field, the negatively charged silk fibroin molecules are driven by the electric field force to migrate directionally towards the central positive electrode and gradually stack up, ultimately constructing a layered tubular silk fibroin material with good interfacial bonding.

[0075] Figure 2 The images show the original morphology and staining results of the layered silk fibroin hydrogels prepared by slab electrophoresis. In the images, a and c show the original morphology of the layered silk fibroin hydrogels prepared by slab electrophoresis; b shows the result of trypan blue staining; and d shows the result of red dye staining. Under the action of the slab electric field, the silk fibroin on the anode side is enriched and has a dense structure, resulting in a darker color after staining. The protein content on the cathode side is low and the structure is loose, resulting in a lighter color after staining.

[0076] Figure 3 The figures show the macroscopic morphology and trypan blue staining results of the electric field-induced layered silk fibroin artificial blood vessels of the present invention. Figures a, b, and c are schematic diagrams of the layered silk fibroin artificial blood vessels prepared according to the present invention. These layered artificial blood vessels exhibit a well-bonded layered tubular structure, with a dense inner layer and a loose, porous outer layer. Figure d shows the trypan blue staining results of a section of the layered artificial blood vessel. Trypan blue is a macromolecular dye, and its color development effect is related to the physical structure of the gel. The silk fibroin hydrogel layered artificial blood vessels prepared according to the present invention have densely packed protein molecules in the inner layer with small pore sizes, resulting in strong physical retention of trypan blue and preventing dye diffusion and loss, leading to a deeper color after staining. The outer layer has a loose protein arrangement and higher porosity, allowing the dye to disperse easily within the pores and be easily eluted, resulting in a lighter color.

[0077] Figure 4 This is a schematic diagram of a layered artificial blood vessel. The outer layer has a high porosity and a wide pore size distribution range (approximately 10-50 μm), which is suitable for the migration and infiltration of smooth muscle cells and fibroblasts. The inner layer is dense with a low porosity and a pore size distribution concentrated in the submicron range (approximately 0.1-1 μm), which is suitable for the adhesion and spreading of endothelial cells.

[0078] Figure 5 This is a SEM microstructure image of the inner layer of the layered silk fibroin artificial blood vessel closest to the anode, magnified at 100×.

[0079] Figure 6 This is a SEM microstructure image of the intermediate transition region of the layered silk fibroin artificial blood vessel, which is relatively close to the anode. The magnification is 100×.

[0080] Figure 7This is a SEM microstructure image of the outward extension of the transition zone of the layered silk fibroin artificial blood vessel, magnified at 60×.

[0081] Figure 8 This is a SEM microscopic image of the outermost layer of the layered silk fibroin artificial blood vessel closest to the cathode, magnified at 60×. The porosity and density of the stent change gradient from the inside to the outside: the inner layer near the electrode has dense protein deposition, a dense structure, and low porosity; the porosity of the intermediate transition zone gradually increases, and the pore size increases gradient; the outer layer forms a high-porosity, interconnected three-dimensional porous network with even larger pore sizes. The overall SEM results visually present the layered characteristics of the tube material, from small to large pores and from dense to loose structures, from the inside to the outside.

[0082] Figure 9 This is a diagram showing the results of the measurement of the inner and outer diameters of the artificial blood vessel. Detailed Implementation

[0083] The technical solution of the present invention will be described more clearly and completely below with reference to specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0084] To enhance understanding of the present invention, certain key technical and scientific terms will be clearly defined below. Unless otherwise specified herein, all other technical and scientific terms shall follow their generally accepted and understood meanings within the art to which this invention pertains. It should be noted that the terminology used herein is intended to describe specific embodiments and not to be construed as limiting.

[0085] Silk fibroin: Silk fibroin is a natural high-molecular-weight protein extracted from the silkworm cocoon layer, mainly composed of 18 amino acids such as glycine, serine, and alanine. In this invention, silk fibroin is used as the single biomaterial for constructing artificial blood vessels. After degumming, dissolution, dialysis, and calcium ion induction treatment, the silk fibroin molecular chains in the solution transform into a β-sheet conformation, forming a stable secondary structure. Furthermore, a unique electrophoretic process is used to construct an artificial blood vessel with a gradient structure—dense on the inside and sparse on the outside, with tight interfacial bonding—achieving a continuous gradient distribution from the intima to the adventitia.

[0086] β-sheet conformation: The β-sheet is a major secondary structure of proteins, formed by the horizontal extension of polypeptide chains, linked by interchain hydrogen bonds to form a lamellar structure; the hydrogen bonds are perpendicular to the long axis of the β-chain. In this invention, through Ca... 2+ Induction pretreatment promotes the transformation of silk fibroin to β-sheet, thereby establishing the mechanical substrate of the material before electrophoretic deposition.

[0087] Electrophoretic deposition: Electrophoretic deposition refers to the process by which charged colloidal particles or macromolecules migrate towards an electrode with opposite charge polarity under the influence of a DC electric field, and undergo charge neutralization, dehydration, or aggregation on the electrode surface, thereby forming a coating or deposited layer. In this invention, a non-traditional cylindrical radial electric field configuration is adopted, with the zinc anode rod located at the center of the mold and the platinum cathode plate located on the inner wall of the mold, thus forming a radial electric field radiating from the center to the periphery. Silk fibroin molecules carry a net charge (negative charge) at a specific pH value and migrate towards the anode (center) under the drive of the electric field. Since the electric field strength decreases with increasing radius, the electric field strength is high and the migration rate is fast near the anode, resulting in rapid protein accumulation to form a dense layer; the electric field strength is weak far from the anode, the protein migration is slow, and diffusion dominates, forming a loose porous layer.

[0088] In some embodiments, the layered artificial blood vessels prepared by the present invention exhibit obvious structural layering characteristics, and can adapt to the layered growth requirements of different functional cells, such as... Figure 4 As shown in Figure a, the inner layer, near the anode, has a dense structure where silk fibroin molecules undergo rapid directional migration and compact deposition under the drive of the electric field, forming a continuous and uniform membrane structure. Its surface is smooth with low porosity, and the pore size distribution is concentrated in the submicron range (approximately 0.1-1 μm). This dense layer effectively mimics the barrier function of the natural vascular endothelium, providing a stable biological interface for the adhesion, spread, and monolayering of endothelial cells. The outer layer, near the cathode, has a looser structure where silk fibroin proteins stack and cross-link in sheet-like or fibrous structures, constructing an open scaffold with a wide pore size distribution (approximately 10-50 μm), high porosity, and good permeability. This structure highly mimics the physical morphology of the extracellular matrix, providing the necessary space and material exchange channels for the migration, infiltration, and angiogenesis of smooth muscle cells and fibroblasts, and supporting the secretion of the extracellular matrix and tissue remodeling.

[0089] Example 1. Optimization of process parameters for the fabrication of layered artificial blood vessels

[0090] The operating parameters in Example 1 are the optimal values ​​obtained through extensive experimental exploration. The relevant preliminary experiments are as follows:

[0091] 1. Voltage

[0092] Voltage is the most critical parameter in the electrophoretic deposition process, directly determining the migration rate of silk fibroin molecules, deposition efficiency, and the microstructure of the deposited layer. In the preliminary experiments of this invention, four voltage gradients of 5V, 15V, 30V, and 50V were set up to systematically evaluate the impact of voltage on the molding effect from the perspectives of structural integrity and micropore characteristics. The results are shown in Table 1.

[0093] Table 1. Effect of electrophoretic voltage on the formation of silk fibroin artificial blood vessels

[0094]

[0095] Under voltages greater than 30V, the silk fibroin gel homogenate in the mold rapidly bubbles and rises. After electrophoresis for the same amount of time, it is observed to exhibit a lotus root-like structure with uneven surface texture and color. During disassembly, it is observed that the inside of the tube shows an unevenly distributed granular structure, and the different aggregates are not tightly connected and easily disperse.

[0096] Extensive testing showed that silk fibroin tubing could be successfully fabricated at voltages ranging from 5V to 30V, but differences existed in structural characteristics and fabrication time. After initially determining the optimal voltage of 15V, this invention further experimented with nearby voltage parameters, ultimately settling the process voltage between 8V and 15V. Voltage parameters within this range can produce tubing with good uniformity and rapid forming. This voltage condition improves the gradient characteristics and biocompatibility of the tubing layer while saving time and cost.

[0097] 2. Electrophoresis time

[0098] The time of a single electrophoresis cycle determines the thickness and bonding strength of each deposition layer, which is a key parameter affecting the overall structural characteristics of the pipe. The project team set up four time gradients of 30s, 1min, 3min, and 5min for comparative experiments, and the results are shown in Table 2.

[0099] Table 2. Effect of single electrophoresis time on the formation effect of silk fibroin artificial blood vessels

[0100]

[0101] After an electrophoresis time of more than 3 minutes, the tubes were observed to have shrunk significantly in volume compared to those with shorter electrophoresis times. They also appeared darker in color, with a tightly wrinkled structure, and had lost their luster and elasticity. Considering the potential for significant inactivation of silk fibroin and increased structural brittleness, this did not meet the usage standards. Conversely, an excessively short electrophoresis time would result in weak bonding and easy dispersion of the silk fibroin on the anode. Ultimately, this invention determined the electrophoresis molding time to be approximately 1 minute and the electrophoresis time for strengthening the structure to be approximately 90 seconds, ensuring the layering requirements and stable structure of the silk fibroin tubes. Through a total of 5 cycles of "electrophoresis-static setting-displacement replenishment," a layered tubular structure with uniform structure and interfacial bonding was gradually constructed.

[0102] Example 2. Method for preparing artificial blood vessels

[0103] 1. Preparation of silk fibroin solution

[0104] 1) Raw material processing: Cut off the silkworm pupae from the cocoons and cut the cocoons into small pieces of about 2-5mm.

[0105] 2) Degumming: Place the silkworm cocoon block in a 0.02M sodium carbonate solution and boil it at 95-100℃ for 30 minutes to remove sericin.

[0106] 3) Cleaning: Rinse the silkworm cocoons repeatedly with clean water 3 times to thoroughly remove any residual alkali and impurities.

[0107] 4) Dehydration and drying: Squeeze out excess water from the cocoon blocks, spread them out flat, and dry them overnight at room temperature.

[0108] 5) Preparation of dissolving solvent: Accurately weigh calcium chloride, ethanol and deionized water in a molar ratio of CaCl2:EtOH:H2O=1:2:8, mix them to prepare Ajisawa reagent, and stir thoroughly until clear.

[0109] 6) Feeding and Dissolving: Add the dried silk fibroin raw material (degummed silkworm cocoon blocks) to the above solvent, ensuring that the raw material is completely submerged. Heat at a constant temperature of 75-85℃ and stir continuously until the raw material is completely dissolved, forming a clear and homogeneous silk fibroin solution.

[0110] 7) Dialysis bag pretreatment: Boil the dialysis bags with a molecular weight cutoff of 3.5 kDa in boiling water for 5 minutes, and then thoroughly clean the inner and outer walls with deionized water to remove possible impurities and plasticizers.

[0111] 8) Preparation of dialysis solution: Prepare sufficient deionized water as the external dialysis solution to ensure that it can completely submerge the dialysis bag.

[0112] 9) Dialysis purification: Place the silk fibroin solution into a pre-treated dialysis bag and tie both ends tightly. Immerse it in deionized water and dialyze continuously for 3 days at 4°C. Replace the dialysis fluid (deionized water) every 12 hours during this period to maintain a gradient of impurity concentration and improve removal efficiency.

[0113] 2. Calcium ions induce β-sheet transition in silk fibroin.

[0114] 1) Solution concentration: The dialysis-purified silk fibroin solution is placed into a concentration tube with a molecular weight cutoff of 3.5 kDa and centrifuged at 4℃ and 5000 r / min until the solution mass concentration reaches about 3% (wt%).

[0115] 2) pH adjustment: Using dilute hydrochloric acid or sodium hydroxide solution, the pH value of the concentrated silk fibroin solution is slowly and precisely adjusted to 7.2±0.2 under magnetic stirring to simulate physiological conditions.

[0116] 3) Ca 2+Solution addition: Add an appropriate volume of 1M CaCl2 stock solution to the pH-adjusted silk fibroin solution while stirring rapidly to bring the final CaCl2 concentration in the solution to 50mM.

[0117] 4) Mixed incubation: The mixed solution containing CaCl2 was incubated in a constant temperature shaker at 37°C and 150 rpm for 24 hours to promote Ca... 2+ The interaction between ions and silk fibroin molecules induces a structural transition to a β-sheet conformation.

[0118] 3. Electrophoretic preparation of layered artificial blood vessels

[0119] 1) Construct a dedicated cylindrical electrophoresis tank: Use a cylindrical acrylic tube (14mm inner diameter) as the molding mold, open shallow grooves on its inner wall, and embed platinum sheets as cathodes. Fix a 1mm diameter zinc rod as the anode at the center of the mold axis. Drill holes in the center of the silicone foam plug at the top and bottom of the mold to ensure that the zinc rod is in the center of the mold, thereby forming a uniform radial electric field around the central anode in the internal cavity of the mold.

[0120] 2) Ca 2+ The treated silk fibroin solution was diluted to a concentration of 2% (w / v) and incubated in a constant temperature water bath at 60°C for 3 hours to complete gelation and form a dense silk fibroin hydrogel. Subsequently, the hydrogel was broken up using a cell disruptor to prepare a flowable homogenous precursor solution for later use.

[0121] 3) Gradient deposition under electric field: First, electrophoretic deposition was performed for about 1 minute at a constant low voltage of 15V, causing silk fibroin molecules to migrate directionally towards the anode and form a preliminary film under the drive of the electric field. During electrophoresis, the current continuously decreased from 0.046A to 0.010A until it stabilized. Then, the power was turned off and the mixture was allowed to stand for about 30 seconds to balance the ion distribution in the system. The device was allowed to cool naturally to room temperature, allowing the deposited gel network structure to relax and stabilize. In actual experiments, it was observed that the inner layer had initially formed at this stage, while the outer layer exhibited an irregular adhesive morphology. If the unstable structure was removed at this point, a dense, semi-transparent film could be observed on the surface of the zinc rod. After standing, the residual homogenate that did not participate in the deposition was removed from the electrophoresis tank. It was observed that its viscosity decreased and its color became transparent, proving the silk fibroin utilization rate of the device. Then, an equal amount of freshly prepared 2% (w / v) silk fibroin gel homogenate was immediately added. The above "electrophoresis-standing-replacement replenishment" cycle was repeated for a total of 4 rounds. After four cycles of "electrophoresis-resting-replacement replenishment," the voltage can be gradually reduced to 11V, with the electrophoresis time decreasing by approximately 6 seconds each time. After the fourth cycle of resting and replenishment, electrophoresis is performed at 10V for 30 seconds. After electrophoresis, the mixture is allowed to rest for 30 seconds, and any residual homogenate in the electrophoresis tank is removed. At this point, the tubular structure has been initially formed. Further overall shaping is required. A small amount of freshly prepared 2% (w / v) silk fibroin gel homogenate is added to the electrophoresis tank, and electrophoresis is performed again at 12V for approximately 90 seconds to stabilize the formed structure, strengthen the interlayer bonding and macroscopic mechanical properties, thereby gradually constructing a layered tubular structure with a smooth surface, uniform texture and structure, and good interfacial bonding. (Note: Under the above operating parameters and the design of low-voltage intermittent electrophoresis, the mold temperature should not rise significantly throughout the process to ensure silk fibroin activity.) The principle of electrophoretic preparation of layered artificial blood vessels is as follows: Figure 1 As shown.

[0122] 4. Post-treatment for fixation and crosslinking

[0123] 1) Preparation of cross-linking solution: Prepare a 2% glutaraldehyde aqueous solution using 1×PBS buffer as the dilution medium, and store it in a refrigerator at 4℃ away from light for later use.

[0124] 2) Crosslinking operation: Immerse the prepared layered silk fibroin tube completely in 2% glutaraldehyde crosslinking solution, ensuring that no air bubbles adhere to the tube, and perform crosslinking treatment at 4℃ in the dark for 12 hours; after crosslinking is completed, take out the tube and rinse it repeatedly with deionized water 3-5 times, each time for 10 minutes, to completely remove residual glutaraldehyde, and obtain the crosslinked tube and store it.

[0125] Further preliminary evaluation of the crosslinking effect was conducted. Small amounts of crosslinked tubing were immersed in deionized water and 1×PBS buffer for at least 24 hours, respectively. The tubing was observed for collapse and deformation, and its shape retention and water resistance were recorded. The results were compared with uncrosslinked tubing. The crosslinked layered silk fibroin tubing showed no collapse or deformation after prolonged immersion in deionized water and 1×PBS buffer, maintaining its intact tubular structure. In contrast, the uncrosslinked control tubing showed edge collapse and structural loosening after prolonged immersion in water. This indicates that 2% glutaraldehyde crosslinking treatment effectively improves the water resistance and structural stability of the layered silk fibroin tubing, demonstrating a good crosslinking effect.

[0126] Example 3. Characterization of artificial blood vessels

[0127] This embodiment further characterizes the silk fibroin layered artificial blood vessel prepared in Example 2, including performing plate electrophoresis and staining characterization on the layered artificial blood vessel prepared by electrophoresis (without post-treatment fixation and cross-linking), and staining characterization on the fixed and cross-linked artificial blood vessel finished product. Details are as follows:

[0128] 1. Staining observation of layered plates and layered artificial blood vessel structures

[0129] 1) Electrophoretic and staining characterization of the layered structure of silk fibroin induced by electric field

[0130] The silk fibroin hydrogel after calcium ion-induced conformational transition was subjected to electrophoresis in a slab electric field to obtain a silk fibroin hydrogel plate, which was then stained and characterized using trypan blue and red dyes. The results are as follows: Figure 2 As shown. Figure 2 Figures a and c show the original morphology of the obtained hydrogel, which exhibits obvious layering: the anodic side is rich in silk fibroin, forming a dense region; the cathode side has a lower protein content, forming a loose region. The trypan blue staining results are shown below. Figure 2 As shown in Figure b, the dense region of the anode has a strong dye retention capacity, resulting in deeper staining; the porous region of the cathode has larger pores, allowing the dye to diffuse and elute easily, resulting in lighter staining. The staining results with red dye are shown below. Figure 2 As shown in Figure d, a consistent pattern emerges: the color is darker on the anode side and lighter on the cathode side.

[0131] The plate electrophoresis experiment showed that the electric field can effectively induce the directional enrichment of silk fibroin, forming a gradient layered structure with a dense anode and a loose cathode. This confirmed the feasibility of constructing a layered structure by electrophoresis and provided direct experimental evidence for the subsequent preparation of gradient artificial blood vessels with a dense inner layer and a loose outer layer by column electrophoresis.

[0132] 2) Staining characterization of silk fibroin layered artificial blood vessels

[0133] Ca 2+The induced silk fibroin gel homogenate was injected into a column electrophoresis tank. Deposition was carried out under a low voltage of 10-20V using intermittent energizing and stepwise feeding, resulting in an integrated tubular embryo with a dense inner layer and a loose outer layer. After glutaraldehyde cross-linking and washing, cross-sectional sections of the artificial blood vessel were taken and stained with 0.4% trypan blue for observation. The results are as follows... Figure 3 As shown, the cross-section of the artificial blood vessel exhibits clear layering characteristics. The inner layer is stained darker and more uniformly, indicating dense protein accumulation and small pores in this region, resulting in strong retention of large-molecule dyes. The outer layer is significantly lighter in color, appearing pale blue, indicating a looser structure and abundant interconnected pores, allowing for easy dye diffusion and elution. These staining results directly confirm that this electrophoresis process can construct a gradient structure artificial blood vessel with a dense inner layer and a loose outer layer, and tight interfacial bonding in one step, achieving a continuous gradient distribution from the intima to the adventitia.

[0134] 3) Scanning electron microscopy (SEM) testing and characterization

[0135] The prepared silk fibroin layered tube samples were dried and then subjected to scanning electron microscopy to observe and record the microstructure of the tube cross-section, the distribution characteristics of interlayer pores, and the differences in microstructure between the inner and outer layers. The results are as follows: Figures 5-8 As shown. Figure 5-8 The images show the SEM morphology at different locations. Figure 5 For the inner layer, Figure 6 , 7 The layers 8 transition sequentially outwards. It is evident that there is a significant gradient difference in pore size and density between the inner and outer layers of the silk fibroin layered tubing: the inner layer corresponds to... Figure 5 The boundary surface of the region shown is relatively smooth, with abundant silk fibroin, a dense structure, and small pores; as it transitions towards the outer layer of the material ( Figure 6 → Figure 7 → Figure 8 The pore size gradually increases, the protein content gradually decreases, and the structure becomes increasingly loose, exhibiting a continuous gradient change in pore size and density from the inside out. SEM characterization results further confirm that the electric field-induced preparation method can successfully construct silk fibroin tubular materials with a layered structure, providing direct microstructural basis for subsequent applications in artificial blood vessels.

[0136] 2. Microstructural characterization of layered silk fibroin artificial blood vessels prepared

[0137] 1) Near the inner electrode region: This region has a dense structure, where silk fibroin molecules undergo rapid directional migration and compact deposition under the drive of an electric field, forming a continuous and uniform membrane structure. Its surface is smooth, with low porosity and pore size distribution concentrated in the submicron range (approximately 0.1-1 μm). This dense layer can effectively mimic the barrier function of the natural vascular intima, providing a stable biological interface for the adhesion, spread, and monolayering of endothelial cells.

[0138] 2) Intermediate Transition Region: This region exhibits a continuous transition from dense to porous. The structure gradually transforms from a continuous membrane to a rough, blocky gel, with noticeable micropores and microcracks appearing. The pore size shows a gradient increase (approximately 1-10 μm), and the structural stiffness exhibits a continuous change. This transition region simulates the mechanical gradient characteristics between the intima and media of natural blood vessels, which is beneficial for stress buffering and transmission.

[0139] 3) Distal electrode region: This region forms a typical three-dimensional interconnected porous network structure. Silk fibroin is stacked and cross-linked in sheet-like or fibrous structures to construct an open scaffold with a wide pore size distribution (approximately 10-50 μm), high porosity, and good permeability. This structure highly mimics the physical morphology of the extracellular matrix, providing the necessary space and material exchange channels for the migration, infiltration, and angiogenesis of smooth muscle cells and fibroblasts, and supporting the secretion of the extracellular matrix and tissue remodeling.

[0140] 3. The inner and outer diameters of artificial blood vessels were determined using an indirect image analysis method.

[0141] After staining a cross-sectional section of the artificial blood vessel, it was placed on a glass slide, and the cross-sectional image was photographed and imported into Photoshop for analysis. In the image, the width of the glass slide was measured to be 79.8 mm (image pixel length) using a ruler tool. The actual width of the glass slide was 25 mm. This established the proportional relationship between the image and the actual size, with the proportionality coefficient k = actual width of the glass slide : width of the glass slide image. The inner diameter of the artificial blood vessel measured in the image was 6.0 mm, and the outer diameter was 29.4 mm. Calculations were performed: actual inner diameter = inner diameter of the artificial blood vessel in the image * k; actual outer diameter of the artificial blood vessel = outer diameter of the artificial blood vessel in the image * k. The calculated actual inner diameter of the vessel was 2.12 mm, and the outer diameter was 9.67 mm. The inner diameter is less than 6 mm, indicating that the stent belongs to the category of small-diameter artificial blood vessels, and the inner diameter meets the application requirements for small vessel repair.

[0142] Example 4. Blood compatibility

[0143] This embodiment further investigates the blood compatibility of the silk fibroin layered artificial blood vessel prepared in Example 2. The experimental methods and results are as follows:

[0144] 1) Blood collection and processing: Fresh whole blood from 9-week-old SD rats was collected, placed in a heparin anticoagulant tube, and gently inverted to mix. The anticoagulant was diluted with 1×PBS at a volume ratio of 4:5 to obtain diluted anticoagulant.

[0145] 2) Sample preparation: Using 10×PBS as the dilution medium, the initial concentration of 6% silk fibroin hydrogel solution was diluted to a series of working solutions with concentrations of 3g / mL, 2g / mL, and 1g / mL. Take 10mL centrifuge tubes, add 5mL of isotonic solution of the silk fibroin sample to each tube in the experimental group, add 5mL of ultrapure water to each tube in the positive control group, and add 5mL of 1×PBS to each tube in the negative control group. Each group was set up in triplicate.

[0146] 3) Incubation: Place the centrifuge tubes of each group in a shaker at 37°C for 30 min, then add 100 uL of diluted anticoagulated blood to each group and incubate in a constant temperature incubator at 37°C for 1 h.

[0147] 4) Centrifugation and absorbance detection: After incubation, centrifuge 10mL centrifuge tubes at 4℃ and 5000r / min for 5min, carefully aspirate the supernatant from each well, and use a UV spectrophotometer to measure the absorbance (OD value) of each well at a wavelength of 545nm, and record the experimental data.

[0148] 5) Calculation and analysis of hemolysis rate:

[0149] The hemolysis rate of each group was calculated based on the OD value. The calculation formula is: Hemolysis rate (%) = (OD value of sample group - OD value of blank control group) / (OD value of positive control group - OD value of blank control group) × 100%; Finally, the hemolytic toxicity and safe concentration range of VPNPs were determined (a hemolysis rate of less than 5% indicates no obvious hemolytic toxicity).

[0150] The results of the hemolysis experiment are shown in Table 3.

[0151] Table 3. Results of Hemolysis Test

[0152]

[0153] The results show that at the three test concentrations of 1%, 2%, and 3%, the hemolysis rates of the silk fibroin (SF) hydrogel solution were 3.27%, 4.12%, and 3.98%, respectively, all significantly lower than the internationally accepted safety threshold of 5%. The hemolysis rates at all three concentrations were within the same low range (3.27%-4.12%), and no increasing trend in hemolysis rate with increasing concentration was observed. This demonstrates that the silk fibroin used in this experiment had no significant hemolytic toxicity within the experimental concentration range, and the prepared silk fibroin layered artificial blood vessel exhibited excellent blood compatibility.

Claims

1. A method for preparing silk fibroin artificial blood vessels with a biomimetic gradient structure, characterized in that, Includes the following steps: S1: Prepare a silk fibroin solution and perform calcium ion induction treatment to obtain a silk fibroin gel homogenate; The calcium ion-induced treatment includes: concentrating the silk fibroin solution, adjusting the pH to 7.2±0.2, and adding CaCl2 stock solution to induce the β-sheet transition of silk fibroin; the final concentration of the CaCl2 stock solution is 50 mM. S2: The silk fibroin gel homogenate obtained in S1 was deposited by intermittent electrophoresis and cross-linked and fixed with glutaraldehyde to obtain a silk fibroin artificial blood vessel with a biomimetic gradient structure. The intermittent electrophoretic deposition includes: 1) The silk fibroin gel homogenate is injected into a cylindrical electrophoresis tank for electrophoretic deposition. After power is turned off and the tank is allowed to stand, silk fibroin gel homogenate is added. The cylindrical electrophoresis tank is formed by using a cylindrical acrylic tube as a mold, with shallow grooves opened on its inner wall and a platinum sheet embedded as a cathode. A zinc rod is fixed at the center of the mold as an anode to form a cylindrical electrophoresis tank. 2) Repeat the electrophoresis, settling and displacement feeding operations in step 1) for a total of 4 rounds; through the electrophoretic deposition process, under the drive of the electric field, a self-assembled integrated structure with a dense inner layer and a loose outer layer is formed, and the inner and outer layers show a continuous gradient transition. In steps 1)-2), the initial voltage for electrophoretic deposition is 15V, and the initial electrophoresis time is 60s; during the cyclic deposition process, the voltage gradually decreases to 11V, and the electrophoresis time decreases by 6 seconds per cycle.

2. The preparation method according to claim 1, characterized in that, In S1, the method for preparing the silk fibroin solution includes: obtaining a purified silk fibroin solution by degumming, dissolving, and dialysis of silkworm cocoons.

3. The preparation method according to claim 2, characterized in that, The dissolving solvent is a mixed solution of calcium chloride, ethanol and deionized water, wherein the molar ratio of calcium chloride, ethanol and deionized water is 1:2:

8.

4. The preparation method according to claim 1, characterized in that, In S1, the reaction conditions include: constant temperature incubation at 37°C and 150 rpm for 24 hours.

5. The preparation method according to claim 1, characterized in that, In step S1, the silk fibroin solution after calcium ion induction treatment is diluted to a concentration of 2% and kept in a constant temperature water bath at 60°C for 3 hours to obtain silk fibroin hydrogel; the silk fibroin hydrogel is then broken to obtain silk fibroin gel homogenate.

6. The preparation method according to claim 1, characterized in that, In S2, each round is paused for 30 seconds.

7. The preparation method according to claim 1, characterized in that, In S2, after the last cycle is completed, there is also a stabilization molding step: electrophoresis is performed again at 12V for 90s.

8. The preparation method according to claim 1, characterized in that, In S2, glutaraldehyde solution is used for cross-linking fixation; the concentration of the glutaraldehyde solution is 2%; the cross-linking time is 12 hours and the cross-linking temperature is 4℃.

9. A silk fibroin artificial blood vessel with a biomimetic gradient structure prepared by the preparation method according to any one of claims 1 to 8.

10. The use of the silk fibroin artificial blood vessel according to claim 9 in the preparation of tissue engineering materials and / or in medical devices for the treatment of cardiovascular and cerebrovascular diseases.

Citation Information

Patent Citations

  • Double bionic orientation artificial small blood vessel and preparation method thereof

    CN115998953A

  • Silk fibroin hydrogels and uses thereof

    WO2010123946A2